2013
DOI: 10.1080/17430437.2013.828902
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer roles, involvement and commitment in voluntary sport organizations: evidence of core and peripheral volunteers

Abstract: The nature and scope of volunteer involvement in sport is well established, however research indicates that involvement in community sport volunteering is under threat (Cuskelly, 2005; Cuskelly, Taylor, Hoye & Darcy, 2005). Trends indicate volunteer hours per individual are decreasing and this can have significant implications for the successful operation of voluntary sport organizations and the subsequent benefits for participants and the communities in which they operate. This paper extends knowledge of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 26 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…Other measures of volunteer commitment examine the quality of volunteers’ ‘post-recruitment participation’ (Catano et al, 2001: 256) by focusing on the ‘willingness of a person to engage in activities that are consistent with and support the organization’s objectives’ (Ringuet-Riot et al, 2014: 120). Given social psychology’s influence on studies of organizational commitment (Cheney et al, 2014), most studies frame commitment as a psychological ‘force that binds an individual to a course of action of relevance to one or more targets’ (Meyer and Herscovitch, 2001: 301), where the course of action implies reduced organizational turnover, less absenteeism, and identification with organizational mission.…”
Section: Volunteer Commitmentmentioning
confidence: 99%
“…Other measures of volunteer commitment examine the quality of volunteers’ ‘post-recruitment participation’ (Catano et al, 2001: 256) by focusing on the ‘willingness of a person to engage in activities that are consistent with and support the organization’s objectives’ (Ringuet-Riot et al, 2014: 120). Given social psychology’s influence on studies of organizational commitment (Cheney et al, 2014), most studies frame commitment as a psychological ‘force that binds an individual to a course of action of relevance to one or more targets’ (Meyer and Herscovitch, 2001: 301), where the course of action implies reduced organizational turnover, less absenteeism, and identification with organizational mission.…”
Section: Volunteer Commitmentmentioning
confidence: 99%
“…This continued commitment to quality service is found across volunteers regardless of age (Misener, Doherty, & Hamm-Kerwin, 2010), volunteer role (Ringuet-Riot, Cuskelly, Auld, & Zakus, 2014), or competitive level (Cuskelly, Harrington, & Stebbins, 2002;Wilks, 2016).…”
mentioning
confidence: 92%
“…Recent research has also demonstrated that the value orientation of a CSO toward helping others in the community may also play an important role in whether people continue their affiliation with that club (Misener & Babiak, ). Preventing any loss of volunteers or members offers important benefits for the CSO, including efficiency; enhanced focus on service delivery; and financial benefit, which can prevent increases in member dues (Ringuet‐Riot, Cuskelly, Auld, & Zakus, ). Thus, positive appraisal of the club from others (i.e., word of mouth) may offer CSOs an important mechanism for strengthening their relationship with members and ensuring positive attachment with the organization.…”
Section: Literature Reviewmentioning
confidence: 99%